2012
DOI: 10.1097/jcn.0b013e31820e2f95
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Cardiovascular Risk Factors, Self-nurturance, and Heart-Healthy Behaviors in Women

Abstract: Most participants were white (94.9%), with a mean age of 45.2 years. Participating women's knowledge of CVRFs was higher than previously reported, but was not significantly (P > .05) related to any heart-healthy behaviors studied. Self-nurturance was moderately correlated with heart-healthy dietary intake scores (P = .002), but did not add further explanatory power for heart-healthy behaviors. The model's key concepts of knowledge and self-nurturance provided minimal explanatory power in this study. These data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Studies continue to show that knowledge does not necessarily translate to changes in behavior. 9,41,49,50 This finding is consistent with other studies, as fewer than half of the women with hypertension who were on medication had their blood pressure under control. 3,51 The mean systolic blood pressure of women diagnosed with hypertension was greater than 140 mmHg.…”
Section: Discussionsupporting
confidence: 90%
“…Studies continue to show that knowledge does not necessarily translate to changes in behavior. 9,41,49,50 This finding is consistent with other studies, as fewer than half of the women with hypertension who were on medication had their blood pressure under control. 3,51 The mean systolic blood pressure of women diagnosed with hypertension was greater than 140 mmHg.…”
Section: Discussionsupporting
confidence: 90%
“…17 Although research has shown that women are becoming more educated with regard to cardiovascular risk factors, this increased awareness has not yet translated into the behavioural changes that would sustain cardiac health. 18 Taken together, these findings suggest that further research focusing on women's cardiac health is required to encourage healthy cardiovascular behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…So although we cannot definitively conclude that healthy behaviors were poorer in Hispanics and black women despite a higher “unknown” calculated risk score, our findings highlight that patients’ motivation for healthy behaviors may be based more on measured weight and self‐perception as overweight or obese. Indeed, prior studies in women have shown that increased knowledge and awareness of CVD risk factors does not necessarily translate into healthier lifestyle behaviors 11, 12. Thus, in the setting of a growing obesity epidemic, it is crucial that health professionals continue to educate patients about heathy BMI and body image to motivate engagement in healthy lifestyle behaviors.…”
Section: Discussionmentioning
confidence: 99%